2015
DOI: 10.1097/cej.0000000000000120
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between education level and mammographic density

Abstract: To further understand the factors that contribute to interindividual variation in mammographic density, we evaluated the relationship between education level and each component of the mammographic density measures. Study participants included 535 women between 40 and 65 years of age who received a mammogram for a population-based twin and family study. Mammographic density was measured from digital mammograms using a computer-assisted thresholding method. To avoid negative confounding by obesity level, we calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Consistent with several studies, 61 , 62 we found that higher levels of education were independently associated with higher MD, suggesting that the MD association with education could not be fully accounted for by measured variables such as BMI and reproductive factors. Other unmeasured lifestyle factors including dietary factors, physical activity, and socioeconomic status-related stress may also contribute and further investigation of these relationships is warranted in future studies.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with several studies, 61 , 62 we found that higher levels of education were independently associated with higher MD, suggesting that the MD association with education could not be fully accounted for by measured variables such as BMI and reproductive factors. Other unmeasured lifestyle factors including dietary factors, physical activity, and socioeconomic status-related stress may also contribute and further investigation of these relationships is warranted in future studies.…”
Section: Discussionsupporting
confidence: 89%
“…However, unfortunately, there were few studies that contained evidence to conclude what the main risk factors were. Reproductive factors including age at first birth were still less favorable for the higher education group in Korea [ 38 ], likewise with western countries [ 39 , 40 ], and the study which supported the decreasing gap in reproductive factors between educational groups could not be found. The gap of age at first birth by educational level among the 1960-1964 birth cohort, the 1965-1969 birth cohort, and the 1970-1974 birth cohort was not different [ 41 ], although the gap of the number of live births by educational level decreased between 1980 and 2000 [ 42 ].…”
Section: Discussionmentioning
confidence: 98%
“…Some studies evaluated the association between the breast density and other factors, such as residential traffic noise, education level, occupation, metabolic syndrome, socioeconomic status, and diabetes. [ 68 159 160 161 162 163 164 165 166 167 168 ] Roswall et al . [ 159 ] found no association between breast density and traffic noise exposure, either residential road or railway noise in a Danish cohort.…”
Section: Epidemiologic Factorsmentioning
confidence: 99%
“…Another study found that the socioeconomic status played a role in determining the amount of fat in breast. [ 160 ] However, another study found early life socioeconomic status, including education and income was not significantly associated with breast density in adulthood. [ 167 ] Lope et al .…”
Section: Epidemiologic Factorsmentioning
confidence: 99%